2012
DOI: 10.4196/kjpp.2012.16.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Albino Rats with Methanolic Fruit Extract ofRandia Dumetorum(L.) Protects against Alcohol Induced Liver Damage

Abstract: Alcohol abuse and its medical and social consequences are a major health problem in many areas of the world. The present study was conducted to evaluate the protective effect of methanolic fruit extract of Randia dumetorum (L.) on alcohol-induced liver damage in rats. Rats were divided into five different groups (n=6), group I served as a control, group II received ethanol (3 ml/100 g/day p.o.), group III served as standard group and received silymarin (50 mg/kg p.o.), group IV and V served as extract treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, serum ALT, LDH and lipid peroxides levels were significantly increased among chronic morphine users. Moreover, long-term use of morphine led to significant decrease in multifunctional detoxification enzymes, including SOD, GST and CAT and reduced the antioxidative defense system and the ratio of GSH/oxidized GSH in an- oxidation in biological material [27]. Therefore, proper treatment is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, serum ALT, LDH and lipid peroxides levels were significantly increased among chronic morphine users. Moreover, long-term use of morphine led to significant decrease in multifunctional detoxification enzymes, including SOD, GST and CAT and reduced the antioxidative defense system and the ratio of GSH/oxidized GSH in an- oxidation in biological material [27]. Therefore, proper treatment is needed.…”
Section: Discussionmentioning
confidence: 99%
“…As MDA is a product of lipid peroxidation, it is commonly used as a biomarker for oxidative stress [35]. When excess alcohol is given to animals, alcohol alters the permeability of the plasma membrane, resulting in enzyme leakage and increased levels of lipid peroxidation products [36]. Lieber [37] demonstrated that unstable permeability due to alcohol insult leads to lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, arecoline is demonstrated to induce hepatotoxicity and testicular toxicity both by generating reactive oxygen species (ROS) [ 11 , 12 ]. Several reports have implicated that excessive generation of these free radicals could result in oxidant stress and disturb antioxidant defense [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%